Nitrogen isotope analysis of aqueous ammonium and nitrate by membrane inlet isotope ratio mass spectrometry (MIRMS) at natural abundance levels. (15th March 2021) - Dyckmans, Jens; Eschenbach, Wolfram; Langel, Reinhard; Szwec, Lars; Well, Reinhard
Abstract : Rationale: Existing methods for the measurement of the 15 N/ 14 N isotopic composition of ammonium and nitrate are either only suitable for labelled samples or require considerable sample preparation efforts (or both). Our goal was to modify an existing analytical approach to allow for natural abundance precision levels. Methods: Published reaction protocols were used to convert ammonium into N2 by NaOBr and nitrate into N2 O by TiCl3 . A membrane inlet system was developed and coupled to an isotope ratio mass spectrometer to allow precise determination of the analytes. Results: Concentrations of ≥35 μmol/L N for both ammonium or nitrate could be analysed for δ 15 N values with precisions of better than 0.9 mUr. While ammonium analyses exhibited a small concentration dependency and an offset of 2.7 mUr at high ammonium concentrations irrespective of the standard isotopic composition, nitrate analysis showed no offset but a blank contribution visible at very low concentrations. Conclusions: The presented method is capable of fast measurement of δ 15 N values in ammonium and nitrate from aqueous samples with reasonable accuracy at natural abundance levels. It will thus facilitate the application of isotopic methods to studies of nitrogen cycling in ecosystems.